Problem związania sądu polubownego przepisami prawa materialnego - Knoppek, Krzysztof (Wydział Prawa i Administracji UAM, 2014)
W doktrynie procesu cywilnego pojawiły się opinie, że sądy polubowne (arbitrażowe) muszą przestrzegać wszystkich przepisów prawa cywilnego (prawa materialnego) na takiej samej zasadzie, jak czynią to sądy państwowe. Pogląd ten jest błędny, gdyż nie można go wyprowadzić ani z przepisów części piątej Kodeksu postępowania cywilnego, ani też z postanowień Regulaminu arbitrażowego UNCITRAL z 2010 r. Poza tym sama idea sądów arbitrażowych polega na tym, że orzekają one na podstawie postanowień umowy, ogólnych zasad prawa, zasad słuszności i ustalonych zwyczajów. Nie są natomiast związane prawem materialnym, muszą jedynie respektować podstawowe zasady porządku prawnego (klauzula porządku publicznego). Strony, którym to nie odpowiada, nie powinny zapisywać swoich spraw cywilnych sądom polubownym.

***Recently, opinions have been voiced in the doctrine of civil procedure that courts of arbitration should observe all provisions of substantive civil law in the same way as state courts of law. This view is incorrect and cannot be derived from the provisions of Part 5 of the Code of Civil Procedure or the provisions of the UNICITRAL Rules of Arbitration of 2010. Further, the very concept of courts of arbitration is that their decisions will be made taking into account mutual contractual obligations of the parties in dispute, the general legal principles, the principle of fairness and equity, and the established custom. What is more, these courts are not bound to follow any provision of substantive law, and must only respect the fundamental principles of the legal order (the public order clause). Thus, if parties are not happy with such a concept of a court of arbitration the should not subject their civil matters to their jurisdiction.
Potential problems arising from subjecting a court of arbitration to the provisions of substantive law
Keywords: sąd polubowny; sąd arbitrażowy; arbitraż; arbiter; związanie sądu polubownego przepisami prawa; court of arbitration; arbitration; arbitrator; subjecting a court of arbitration to legal provisions